The Role of Celebrity Endorsement and Brand Awareness in Forming Purchase Intention: The Influence of Brand Image as an Intervening Variable - Chicha Fahriana; Heri Pratikto; Titis Shinta Dhewi (International Journal of Asian Business and Management, 2024)
This study aims to explore the influence of celebrity endorsement and brand awareness on consumers' purchase intentions, with brand image acting as a mediating variable. The importance of this research stems from addressing a gap identified in existing literature. A quantitative approach was employed, utilizing purposive sampling as the non-probability technique for participant selection. Data were collected through surveys using a 5-point Likert scale, and the final sample included 385 respondents. The data analysis was conducted with the SmartPLS (Partial Least Squares) method. The results indicate that both celebrity endorsement and brand awareness positively and significantly affect purchase intention. Additionally, both factors also positively influence brand image. However, brand image does not act as a mediator between celebrity endorsement, brand awareness, and purchase intention, contrary to the initial hypothesis